Evaluation of nitrogen transfer from nodulate alfafa to associated grasses under field conditions. - Burity, Hélio A.; Faris, Mohamaed A.; Coulman, Bruce E.; Ta, Trung C. (Pesquisa Agropecuaria Brasileira, 2014)
The contribution of N2 . fixation to the nitrogen nutrition of alfafa (Medicaga sativa L.) and transference of N to associated grasses timothy (Phleum pratense L.) and bromegrass (Bromus inennis Leyss.) when grown in mixture, were estimated using the 15N isotope dilution technique. The percentage of alfafa N derived from atmosphere (% Ndfa) increased throughout the growing seasons ranging from 63 to 83%. The total amount of N2 fixed by alfafa has shown a pattern similar to % Ndfa with slight increases to the absolute amount of N2 fixed by alfalfa in mixed stands. N transfer from alfafa to an associated grass was evident, and contributed 26, 46 and 38% of the total annual N yield of grass and represented an absolute amount of about 5.0, 20.0 and 19.0 kg. ha-1 during the first, second and third year. The results showed that all grass species benefitted from N transfer from alfafa, although the early maturity species with greater competitive ability are slightly more responsive.